Positioning of media economic framework for novel media in the field of project business - Iskander, N.; Lugmayr, Artur (2011)
New Media across the Internet is a growing phenomenon in this digital age. The explosive growth of online social networking firms creates business opportunities in the Internet media. These business opportunities require a definitive business models approach because of the rapid growth of these firms (e.g. Facebook) engaged in Internet media over a short period of time. This approach needs an assessment of a media economic framework of new media in the Internet. The goal of this paper is to formulate such a media economic framework by applying literature based on project business findings. This framework will consist of four distinct areas i.e. a. Print Media, b. Audio Media, c. Motion Pictures Media, d. Visual Media. However, for analysis purposes only two i.e. motion-picture and visual medias will be undertaken. The purpose of the framework will be to generate evaluation metrics from which performance tests will be conducted to deduce results that will justify the definitive business models approach. The paper will limit itself with the formulation of the media economic framework from both project business and media economics perspectives, highlights its key aspects, discuss the findings of the literature, identify similarities between the two perspectives, explore project business domain at length and develop its perception and its relation to the media economic framework, provide an analytical study of the scope of media economic framework in project business and finally conclude with a set of recommendations for future research. © 2011 ACM.